Accessing Malay manuscripts worldwide through ICT: the union catalogue project - Wan Mamat, Wan Ali (Southeast Asia Library Group, 2013)
Malay manuscript collections are found all over the world. The majority of the collections are located in the country of their origins like Malaysia, Indonesia, Brunei and Singapore. Some can be found in countries where Malays form a minority like Sri Lanka and South Africa. A significant number can be found in foreign countries of the West and East, especially in major libraries in countries like The Netherlands, United Kingdom, France, Germany and Japan. Most of the manuscripts have been catalogued by the institutions where they are being held, but not all information has been published in catalogue book or electronic format. Even where published catalogues are available, the distribution of these printed catalogues may have been very limited. Besides this, though libraries and museums are supposed to take full advantage of ICT in order to promote their collections, unfortunately - with regard to Malay manuscript collections – many institutions still do not use ICT to an optimal extent. In order to promote Malay manuscripts that are available worldwide as an important source for research, ICT should be used in the best possible ways.